The TRPC5 receptor as pharmacological target for pain and metabolic disease - Khare, Pragyanshu; Chand, Jagdish; Ptakova, Alexandra; Liguori, Renato; Ferrazzi, Fulvia; Bishnoi, Mahendra; Vlachova, Viktorie; Zimmermann, Katharina (Pharmacology & Therapeutics, 2024)
The transient receptor potential canonical (TRPC) channels are a group of highly homologous nonselective cation channels from the larger TRP channel family. They have the ability to form homo- and heteromers with varying degrees of calcium (Ca2+) permeability and signalling properties. TRPC5 is the one cold-sensitive among them and likewise facilitates the influx of extracellular Ca2+ into cells to modulate neuronal depolarization and integrate various intracellular signalling pathways. Recent research with cryo-electron microscopy revealed its structure, along with clear insight into downstream signalling and protein-protein interaction sites. Investigations using global and conditional deficient mice revealed the involvement of TRPC5 in metabolic diseases, energy balance, thermosensation and conditions such as osteoarthritis, rheumatoid arthritis, and inflammatory pain including opioid-induced hyperalgesia and hyperalgesia following tooth decay and pulpitis. This review provides an update on recent advances in our understanding of the role of TRPC5 with focus on metabolic diseases and pain.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Calcium homeostasis; Energy expenditure; Glucose homeostasis; Inflammatory pain; Metabolism; TRPC5